Longitudinal analysis of T-cell receptor repertoires reveals persistence of antigen-driven CD4+ and CD8+ T-cell clusters in systemic sclerosis. Issue 117 (February 2021) - Servaas, N.H.; Zaaraoui-Boutahar, F.; Wichers, C.G.K.; Ottria, A.; Chouri, E.; Affandi, A.J.; Silva-Cardoso, S.; van der Kroef, M.; Carvalheiro, T.; van Wijk, F.; Radstake, T.R.D.J.; Andeweg, A.C.; et al.
Abstract: The T-cell receptor (TCR) is a highly polymorphic surface receptor that allows T-cells to recognize antigenic peptides presented on the major histocompatibility complex (MHC). Changes in the TCR repertoire have been observed in several autoimmune conditions, and these changes are suggested to predispose autoimmunity. Multiple lines of evidence have implied an important role for T-cells in the pathogenesis of Systemic Sclerosis (SSc), a complex autoimmune disease. One of the major questions regarding the roles of T-cells is whether expansion and activation of T-cells observed in the diseases pathogenesis is antigen driven. To investigate the temporal TCR repertoire dynamics in SSc, we performed high-throughput sequencing of CD4 + and CD8 + TCRβ chains on longitudinal samples obtained from four SSc patients collected over a minimum of two years. Repertoire overlap analysis revealed that samples taken from the same individual over time shared a high number of TCRβ sequences, indicating a clear temporal persistence of the TCRβ repertoire in CD4 + as well as CD8 + T-cells. Moreover, the TCRβs that were found with a high frequency at one time point were also found with a high frequency at the other time points (even after almost four years), showing that frequencies of dominant TCRβs are largely consistent over time. We also show that TCRβ generation probability and observed TCR frequency are not related in SSc samples, showing that clonal expansion and persistence of TCRβs is caused by antigenic selection rather than convergent recombination. Moreover, we demonstrate that TCRβ diversity is lower in CD4 + and CD8 + T-cells from SSc patients compared with memory T-cells from healthy individuals, as SSc TCRβ repertoires are largely dominated by clonally expanded persistent TCRβ sequences. Lastly, using "Grouping of Lymphocyte Interactions by Paratope Hotspots" (GLIPH2), we identify clusters of TCRβ sequences with homologous sequences that potentially recognize the same antigens and contain TCRβs that are persist in SSc patients. In conclusion, our results show that CD4 + and CD8 + T-cells are highly persistent in SSc patients over time, and this persistence is likely a result from antigenic selection. Moreover, persistent TCRs form high similarity clusters with other (non-)persistent sequences that potentially recognize the same epitopes. These data provide evidence for an antigen driven expansion of CD4 + /CD8 + T-cells in SSc. Highlights: The CD4 + and CD8 + TCRβ repertoire in SSc patients is highly stable over time. Persistent TCRβs are a result of antigenic selection rather than bystander activation. SSc TCRβ repertoires are less diverse than healthy memory repertoires. Clusters of TCRβs with potentially similar specificities are present in SSc over time.